2018
DOI: 10.1016/j.clgc.2018.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Hematologic Toxicity From Radium-223 Therapy for Bone Metastases in Castration-Resistant Prostate Cancer: Risk Factors and Practical Considerations

Abstract: Radium-223 dichloride is an α-emitting radiopharmaceutical that localizes to bone matrix and is approved for the treatment of patients with metastatic castration-resistant prostate cancer (CRPC) and symptomatic bone metastases. The cumulative impact of Ra-223 and other therapeutic agents for metastatic CRPC on myelosuppression in bone marrow is unknown. The phase 3 randomized, double-blind, placebo-controlled ALSYMPCA trial of Ra-223 in patients with CRPC and symptomatic bone metastases demonstrated a signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…Additionally, anemia of any grade was observed in 18% of this study cohort, which was similar to the rate observed in the ERA 223 trial (13%), but lower than observed in the ALSYMPCA trial (31%). Interestingly, prior docetaxel has been associated with a higher incidence of anemia, across several clinical trials and several retrospective studies, and aligns with the observation that the ALSYMPCA trial had higher rates of both docetaxel pretreated patients and anemia than patients in the present study [7,12,[16][17][18].…”
Section: Plos Onesupporting
confidence: 88%
“…Additionally, anemia of any grade was observed in 18% of this study cohort, which was similar to the rate observed in the ERA 223 trial (13%), but lower than observed in the ALSYMPCA trial (31%). Interestingly, prior docetaxel has been associated with a higher incidence of anemia, across several clinical trials and several retrospective studies, and aligns with the observation that the ALSYMPCA trial had higher rates of both docetaxel pretreated patients and anemia than patients in the present study [7,12,[16][17][18].…”
Section: Plos Onesupporting
confidence: 88%
“…Moreover, it would have been interesting to verify the results of bone marrow evaluations in the patients with marrow failure reported in the ALSYMPCA trial [1] or the REASSURE study [20], to exclude other missed cases of t-AML. Physicians should be aware about the possibility of a t-AML arising in patients treated with 223 Ra developing cytopenia or signs of bone marrow failure [22]. On this path, the authors call for further research to improve scientific knowledge on 223 Ra-therapy long-term effects, also through multicentric Phase IV postmarketing surveillance and pharmacovigilance studies.…”
Section: Discussionmentioning
confidence: 99%
“…There is an increasing use of RNT for patients with extensive bone metastases from castration-resistant prostate cancer, for example with 223 Ra or radiolabelled prostate-specific membrane antigen (PSMA) ligands (possibly even subsequently) [39,40]. These tracers do not actively target haematological cells, but the circulation phase and accumulation in normal bone or bone metastases can result in significant dose to bone marrow [41]. A study used baseline [ 18 F]fluorocholine(FCH) PET, typically used to detect metastatic recurrent prostate cancer, to determine bone tumour infiltration and was thereby able to predict haematological toxicity in metastatic prostate cancer patients who received 223 Ra therapy [42].…”
Section: Bone Marrowmentioning
confidence: 99%